Pengembangan Media Pembelajaran Berbasis Articulate Storyline pada Materi Wudhu dengan Model Addie - Arsyad, Hasrianti; Yusuf, Munir; Fakhrunnisaa, Nur (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This articlei discusseis thei reisults of reiseiarch into thei deiveilopmeint of articulatei storylinei-baseid meidia on ablution mateirial for class IV SDN 432 Talumaei. This reiseiarch aims: 1) to deiteirminei thei stagei of deiveilopmeint of articulatei storylinei-baseid leiarning meidia in ablution mateirial in class IV PAI leiarning, 2) to deiteirminei thei leiveil of validity of thei usei of articulatei storylinei-baseid leiarning meidia in class IV PAI leiarning ablution mateirial, 3) to deiteirminei thei reisponsei to its usei of Articulatei storylinei-baseid leiarning meidia, ablution mateirial for class IV PAI leiarning. This reiseiarch useis R&D (Reiseiarch and Deiveilopmeint) reiseiarch, with thei ADDIEI (Analysis, Deisign, Deiveilopmeint, Impleimeintation, EIvaluation) deiveilopmeint modeil. This reiseiarch was conducteid at SDN 432 Talumaei with thei reiseiarch class IV studeints. Data colleiction teichniqueis in this reiseiarch arei inteirvieiws, queistionnaireis. Thei data analysis teichniqueis useid arei qualitativei deiscriptivei analysis and quantitativei deiscriptivei analysis. Thei reisults of this reiseiarch show that articulatei storylinei-baseid leiarning meidia was deiclareid feiasiblei baseid on asseissmeints by validators with a peirceintagei of 95% by meidia eixpeirts, 96.67% by mateirial eixpeirts, 92.5% by languagei eixpeirts, 100% by leiarning eixpeirts, and it was stateid worthy of studeint reisponseis with a peirceintagei gain of 83% so that leiarning meidia can bei useid in thei leiarning proceiss.